Positional In-Match Running Demands of University Rugby Players in South Africa - Donkin, Cameron (Front Psychol, 2020)
The implementation of the Varsity Cup rugby competition among South African universities has sparked interest in university rugby cultures around the country. The Varsity Cup has established itself as one of the most important rugby competitions for full-time students. The development of specific conditioning programs for rugby players requires a thorough understanding of the game and the unique demands of playing positions. Therefore, the study aimed to investigate the in-match running demands of South African university rugby players by using GPS during match play for primary and secondary positional groups. Rugby players (n = 40) from two universities were assessed during match play (n = 17) over a competitive season by using GPS. Players were grouped into two primary positional groups, forwards (n = 22) and backs (n = 18), and five secondary positional groups, tight forwards (n = 14), loose forwards (n = 8), half backs (n = 5), inside backs (n = 6), and outside backs (n = 7). The GPS analysis provided the following match-play movements: total distance, high-speed meters, maximum velocity, match intensity, the number of accelerations and decelerations, and velocity zone. Halfbacks recorded the highest total distance (6620.9 ± 784.4 m; p = 0.02) and match intensity (77.7 ± 11.6 m/min; p = 0.01). Outside backs recorded the highest maximum velocity (8.385 ± 1.242 m/s; p = 0.00). Loose forwards registered the highest number of accelerations (385.5 ± 122.1) and decelerations (378.7 ± 108.1). Backs and their specific subgroups play at and within high velocity thresholds, significantly higher (p = 0.01) than that of the forwards. Forwards tend to be involved in a higher amount of accelerations and decelerations during match play, suggesting that forward play is at close quarters to the opposition. During university rugby matches, the backs covered greater distances and speeds than the forwards, whereas the forwards achieved more accelerations and decelerations than backs. Results from the study can assist Varsity Cup strength and conditioning coaches to prepare players for the position-specific demands of the competition.